Acute Liver Failure: Cohort of patients treated at the La Raza National Medical Center Specialty Hospital. - Karenn Garcia-Campos; Francisca Martinez-Silva (Annals of Hepatology)
Introduction and Objectives: Identify the clinical, biochemical behavior, complications and mortality of patients with acute liver failure admitted to the hospital. Materials and Patients: A descriptive, cross-sectional and retrospective observational study was carried out on all patients who entered the gastroenterology service of the CMN La Raza Specialty Hospital from April 2022 to April 2024 with a diagnosis of Acute Liver Failure. Information was taken from the electronic medical, radiological and laboratory care records. Taking demographic data, clinical and biochemical behavior of the patients, the presence of complications, comorbidities and the outcome. The results were analyzed using measures of central tendency to obtain percentages and arithmetic mean. Results: 78 patients admitted to the service in this period were registered, of them 11 women (14%) and 67 men (85.4%). The average age was 34.7 years (18-64 years). The most frequent cause was attributable to Hepatitis A virus (61%), autoimmune hepatitis (9.75), acute fatty liver of pregnancy (7.3%); However, in 9.7% of patients, no cause was determined (Graphic 1). More than half of the patients presented without other comorbidity (58.5%). Of the patients with comorbidities, Systemic Arterial Hypertension was the most frequent in 17%. The most frequent complications were acute kidney injury (78%), ascites (14.6%), metabolic acidosis (14.6%); upper gastrointestinal bleeding (12.1%) and diffuse cerebral edema (9.7%). Some patients required some type of renal function replacement therapy, such as Hemodialysis (19.5%). 7.3% required therapy with PRISMA and 34.1% with MARS. Mortality is significant in 48.7% of patients despite therapy. Of the patients, 28.2% met transplant criteria, and only 25% of these were transplanted (Table 1). Conclusions: We have noticed an increase in the incidence of Acute Liver Failure in general, highlighting this in young patients of economically productive age and reproductive age, which emphasizes enhancing prevention campaigns in vaccination against virus A in this population, being the cause, of more frequent in our cohort.